The effects of knee joint kinematics on anterior cruciate ligament injury and articular cartilage damage. Issue 5 (3rd April 2016) - Orsi, Alexander D.; Chakravarthy, Srinath; Canavan, Paul K.; Peña, Estefanía; Goebel, Ruben; Vaziri, Askhan; Nayeb-Hashemi, Hamid
Abstract : This study determined which knee joint motions lead to anterior cruciate ligament (ACL) rupture with the knee at 25° of flexion. The knee was subjected to internal and external rotations, as well as varus and valgus motions. A failure locus representing the relationship between these motions and ACL rupture was established using finite element simulations. This study also considered possible concomitant injuries to the tibial articular cartilage prior to ACL injury. The posterolateral bundle of the ACL demonstrated higher rupture susceptibility than the anteromedial bundle. The average varus angular displacement required for ACL failure was 46.6% lower compared to the average valgus angular displacement. Femoral external rotation decreased the frontal plane angle required for ACL failure by 27.5% compared to internal rotation. Tibial articular cartilage damage initiated prior to ACL failure in all valgus simulations. The results from this investigation agreed well with other experimental and analytical investigations. This study provides a greater understanding of the various knee joint motion combinations leading to ACL injury and articular cartilage damage.